Implementasi Inovasi Teknologi Sistem Penyediaan Hijauan Makanan Ternak Di Lahan Kering di Yogyakarta - Supriadi, Supriadi (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2015)
The successful development of agriculture depends on the success in optimizing the utilization of natural resources owned. Potential sources of forage availability based on land resources is possible in each area there will be a difference, this difference is very important to be in the know as it will determine the further development model farm. From the results of the identification of problems in dryland farm development include (1) The availability of food in the dry season is very less; (2) Distance birth (calving interval) long; (3) low soil fertility and limited manpower. Fermented corn husk and rice straw fermentation can increase the protein content and improve digestibility. Provision of forage with corn planting pattern thinning meeting four times to get forage 22.5 tonnes / ha and corn dry as much as 4.2 tons / ha. Improvements pattern plants can guarantee the availability of forage throughout the year. Hermada grass planting in dry soil can produce forage 35.56 tonnes / ha or can accommodate 3.3 livestock units / year. Increased production of rice straw IP 300 and IP 400 can increase the production of rice straw up to 30%. Feed quality improvements at the farm level by fermenting corn husks with curing for 14 days plus 2% urea may contain crude protein ranged from 4.8% to 8.4%. Fermented rice straw by addition of 1 kg of probiotics and 2 kg of urea to 500 kg of dry rice straw can produce quality hay-scented and soft textured.